Previdência rural sob uma perspectiva de gênero: uma análise para as regiões do Brasil - Souza, Edinéia Lopes da Cruz (2014)
The aim of this study was to analyze the access to rural security from the perspective of gender. The 1988 Constitution was a milestone in the history of women, for it has provided the women the right to rural retirement age, already granted to men. In the discipline of law, began to consider women aged 55 or older and men aged 60 years or older, able to benefit as special insured, provided that they would prove to have bond with the system of family economy. To meet the proposed goal it was used data from the National Survey by Household Sampling (PNAD) in 2001 and 2009. To do so, a proxy that could approximate the real number of insured rural special was created; from the proxy, descriptive statistics from the data collected was carried out. The results showed that during the analyzed period, the pensions paid by rural age had a positive increase of 26% for women, which was higher than men, who increased 21%.However, in terms of access, the data point to a disfavoring towards the women group in relation to the men group because in the group of women suitable to apply for the benefit, on average 74% were retired, in males the retirees average was higher, 84% during the period. In the ex-post evaluation of the rural pension policy results signaled a recurrent inequality between women and men in access to benefit more than two decades after the change in legislation. A positive aspect is that the proportion of the inequality of women relative to men in terms of amounts of pensions paid was reduced during the period. Among the regions, there was emphasis in terms of number of rural retired employees in the Northeast and South regions, due to the strong presence of family farmers. By targeting gender analysis from the perspective of transversality of pension policy, it was identified the influence of other variables, namely: color (or race) and education level, in retirement access of the rural population. Much of the rural population is composed of black people (brown and black), that is the result of historical legacy and that is configured most representative in the Northeast and to a lesser extent in the South. It is believed that factors with low education and color (or race), in addition to regional characteristics, influence on inequalities in access to the benefit. Finally, with respect to women, it is believed that their disfavoring in relation to men in this policy is due to lack of recognition of their work considering the sexual division of labor in the rural itself. Thus, it is suggested the articulation of various sectors as INSS, SPM, MDA, FUNAI, in the pursuit of greater efficiency and effectiveness of public policy. Moreover, power relations expressed in labor relations and which takes effect with the invisibility of female participation in rural labor has influence upon the access to public policies. In addition to changes in the operationalization of welfare policy, there should be inserted in the policy management other components such as region, race, ethnicity; it is also necessary changes in the informal intrafamily relationships, which in rural areas are settled in power relations between genders and strengthened especially in the gender division of labor.